2003
DOI: 10.1074/jbc.m208742200
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Contamination in Recombinant Human Heat Shock Protein 70 (Hsp70) Preparation Is Responsible for the Induction of Tumor Necrosis Factor α Release by Murine Macrophages

Abstract: Using commercially available recombinant human heat shock protein 70 (rhHsp70), recent studies have shown that rhHsp70 could induce the production of tumor necrosis factor ␣ (TNF␣) by macrophages and monocytes in a manner similar to lipopolysaccharide (LPS) e.g. via CD14 and Toll-like receptor 4-mediated signal transduction pathway. In the current study, we demonstrated that a highly purified rhHsp70 preparation (designated as rhHsp70 -1) with a LPS content of 1.4 pg/ g was unable to induce TNF␣ release by RAW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
281
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 367 publications
(297 citation statements)
references
References 32 publications
(46 reference statements)
11
281
2
3
Order By: Relevance
“…As mentioned above, HSP themselves can stimulate the maturation of APC and the production of proinflammatory cytokines [10,30,31], and the HSP effect has to be carefully distinguished from effects of contaminations like LPS [32,33]. In our experiments, complexing Hsp70 with the antigenic peptide was crucial for an enhanced proliferation of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As mentioned above, HSP themselves can stimulate the maturation of APC and the production of proinflammatory cytokines [10,30,31], and the HSP effect has to be carefully distinguished from effects of contaminations like LPS [32,33]. In our experiments, complexing Hsp70 with the antigenic peptide was crucial for an enhanced proliferation of CD4 + T cells.…”
Section: Discussionmentioning
confidence: 67%
“…Different mechanisms explaining the effect of HSP have been discussed, including an increased uptake and enhanced intracellular processing of chaperoned peptide by APC [18,28,29], a direct effect of HSP on APC [6, 10,[29][30][31] or an effect only due to microbial contaminations of the HSP preparation [32,33]. HSP:peptide complexes can be released by necrotic cells [2] and taken up by APC via specific receptors (reviewed in [34]).…”
Section: Discussionmentioning
confidence: 99%
“…LPS has been reported to activate various types of lymphocytes via TLR2 signaling [57]. To exclude possible LPS contamination, we pre-treated the SjHSP60, SJMHE1, and OVA 323-339 with polymyxin B-agarose as described previously [58].…”
Section: Prediction Of Epitopes and Synthesis Of Peptidesmentioning
confidence: 99%
“…and Figueiredo and coworkers have recently reported that 'Hsp70' expressed in eukaryotic cells is still active as a T lymphocyte stimulator [106], refuting the work of Gao and Ye [103,104]. In addition, the work of Lehner and co-workers has comprehensively ruled out LPS as a contributor to the cellular effects produced by M. tuberculosis Hsp70 [84].…”
Section: Hsp70 Familymentioning
confidence: 94%
“…Post-translational modifications (which will not be present in recombinant proteins prepared in E. coli) could influence activity. A more serious issue hindering the study of the Hsp70 system is a small number of papers which claim that the activity of 'Hsp70' protein is due to either contaminating E. coli components such as LPS [103] or flagellin [104], or to nucleotides left over as part of the isolation procedure [105]. The flagellin paper [104] focused on Hsp70 stimulation of T cells.…”
Section: Hsp70 Familymentioning
confidence: 99%